Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/s12888-014-0360-2
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of mental health interventions for survivors of systematic violence in Kurdistan, Northern Iraq

Abstract: BackgroundExperiencing systematic violence and trauma increases the risk of poor mental health outcomes; few interventions for these types of exposures have been evaluated in low resource contexts. The objective of this randomized controlled trial was to assess the effectiveness of two psychotherapeutic interventions, Behavioral Activation Treatment for Depression (BATD) and Cognitive Processing Therapy (CPT), in reducing depression symptoms using a locally adapted and validated version of the Hopkins Symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(132 citation statements)
references
References 55 publications
3
120
0
6
Order By: Relevance
“…Abbreviation: CI, confidence interval; df , degrees of freedom; SD, standard deviation. Bolton 2014a(i): BMC Psychiatry , behavioral activation experimental condition versus control; Bolton 2014a(ii): BMC Psychiatry , cognitive processing therapy experimental condition versus control; Bolton 2014b, PLoS Medicine , common elements treatment approach (CETA) experimental condition versus control; Weiss 2015(i): BMC Psychiatry , cognitive processing therapy experimental condition versus control; Weiss 2015(ii): BMC Psychiatry , common elements treatment approach (CETA) experimental condition versus control.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Abbreviation: CI, confidence interval; df , degrees of freedom; SD, standard deviation. Bolton 2014a(i): BMC Psychiatry , behavioral activation experimental condition versus control; Bolton 2014a(ii): BMC Psychiatry , cognitive processing therapy experimental condition versus control; Bolton 2014b, PLoS Medicine , common elements treatment approach (CETA) experimental condition versus control; Weiss 2015(i): BMC Psychiatry , cognitive processing therapy experimental condition versus control; Weiss 2015(ii): BMC Psychiatry , common elements treatment approach (CETA) experimental condition versus control.…”
Section: Figurementioning
confidence: 99%
“…Systematic reviews (Clarke et al 2013, van Ginneken et al 2013) have demonstrated that these innovations have been associated with moderate to large effects on clinical and social outcomes in individuals with CMDs. More recently, global mental health has followed trends from high-income countries (HICs), moving toward transdiagnostic, or common element, approaches that address the barrier of focusing on treating a single disorder (Bolton et al 2014a,b; Murray et al 2014). Transdiagnostic treatments teach a set of common practice elements that can be delivered in varying combinations to address a range of problems.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have examined the feasibility of training primary care staff [30] or paraprofessionals [15] to deliver EBPs, and some have found evidence for effectiveness [15,31]. A growing body of research has begun to examine and compare training models and methods [32,23], but there is often insufficient infrastructure to retain trained personnel after a particular project has been completed [17].…”
Section: Personnelmentioning
confidence: 99%
“…CPT is a cognitive-behavioral therapy that was first developed to treat trauma symptoms in female survivors of sexual violence. Most recently, CPT has been implemented in Iraq [3840], the Democratic Republic of Congo (DRC); [41••, 42], and an urban community health center outside Boston [43, 44]. One of the first global randomized controlled trials of CPT occurred in the DRC for survivors of sexual violence [41••].…”
Section: Evidence-based Treatments For Ptsd: Beyond the Academic Medimentioning
confidence: 99%
“…This study added a significant contribution to our understanding of the treatment of ongoing trauma: namely, that individuals living in high-violence areas or who are experiencing chronic trauma can achieve significant reduction in PTSD symptoms by receiving CPT, compared to individual supportive therapy, similar to previous trials conducted in low-conflict regions. Additionally, a randomized controlled trial of adapted CPT was performed in Iraq with Kurdish survivors of torture [38]. CPT was effective at reducing depression, dysfunction, anxiety, PTSD symptoms, and traumatic grief, providing support for the finding that CPT (compared to the wait-list control) is not only effective at reducing PTSD symptoms alone, but has secondary effects at reducing other psychopathology symptoms.…”
Section: Evidence-based Treatments For Ptsd: Beyond the Academic Medimentioning
confidence: 99%